On the Potentials and Limitations of Attributing a Small‐Scale Climate Event. Issue 16 (20th August 2022) - Matte, Dominic; Christensen, Jens H.; Feddersen, Henrik; Vedel, Henrik; Nielsen, Niels Woetmann; Pedersen, Rasmus A.; Zeitzen, Rune M. K.
Abstract: Intense convective storms can be hazardous when occurring over large populated cities. In a changing climate, decision makers and the general public increasingly need to be able to better understand if and to what extent these storms are influenced by anthropological climate change and what to expect as climate continues to warm. Unfortunately due to their limited ability to resolve small‐scale features in models, convective storms remain a challenge to the modeling community. Here, we use a forecast‐ensemble based method using a convection permitting model with full data‐assimilation, to assess the risk of exceeding certain precipitation thresholds related to a critical cloudburst event that occurred over Copenhagen, Denmark. Our results show that this set‐up is representing well the overall observed intensities. By adapting a pseudo‐global warming approach, we show that both the risk for flooding and the risk for reaching unprecedented precipitation intensity increases resulting from further warming. Plain Language Summary: Cloudburst events are extremely damaging, especially when they hit a city center such as the one impacting Copenhagen, Denmark on 2 July 2011. When something like this happens, the public awareness immediately rises, and many questions emerge such as for example, "How is this related to climate change?" Attributing climate change to these kinds of events is challenging since sensitivity to the initial and driving conditions completely undermine state‐of‐the‐art attribution endeavors to address climate change. Here, by addressing different global warming levels we are taking an alternative modeling approach to study such a cloudburst. Specifically, we simulated this event using an esteemed state‐of‐the‐art numerical weather prediction modeling system currently in use at multiple national weather services in Europe. In this study, using a storyline approach, we show that both the risk for flooding and the risk for reaching unprecedented precipitation intensities increase as climate warms. Specifically, we here demonstrate that the risk of occurrence of such an event is found to be almost double to what could have been realized without anthropogenic warming present. Key Points: A risk was identified for a very intense and localized precipitation event using a mesoscale operational weather prediction model We relate the risk level of a heavy‐precipitation event to climate change The risk of occurrence of a very heavy precipitation increases with the level of warming